1984
DOI: 10.1136/bmj.288.6414.349
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against human insulin.

Abstract: Sera from 680 non-diabetic subjects with suspected autoimmune disease were screened for 13 different antibodies. Of the 582 sera found to contain these antibodies, nine bound insulin in an IgG specific enzyme linked immunosorbent assay (micro ELISA). Four of the sera bound human, porcine, and bovine insulins and five bound exclusively human insulin. "Cold" human, porcine, and bovine insulins each displaced, in a dose dependent manner, the four sera which bound all three insulins, but only human insulin displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Thus, both of these studies reported a frequency of elevated insulin binding that is below that presented here (at least 50%). Wilkin and Nicholson 35 have previously reported a small percentage of individuals with insulin autoantibodies that bind human, but not porcine, insulin. Because these antibodies would not be detected in our assay, one would have predicted a slightly lower percentage of positive sera at diagnosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both of these studies reported a frequency of elevated insulin binding that is below that presented here (at least 50%). Wilkin and Nicholson 35 have previously reported a small percentage of individuals with insulin autoantibodies that bind human, but not porcine, insulin. Because these antibodies would not be detected in our assay, one would have predicted a slightly lower percentage of positive sera at diagnosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin autoantibodies detectable by ELISA in nondiabetic individuals are frequently monoclonal and directed to human insulin, whereas antibodies in insulin-treated individuals are usually polyclonal and do not discriminate among species (1,27,28). Noncompetitive-binding ELISAs have been used to analyze binding kinetics; however, the validity of this approach has been disputed (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…I nsulin-dependent (type I) diabetes mellitus has been reported to be associated with insulin autoantibodies detectable by radiobinding assays up to 40% of the time in individuals who are <20 yr of age (1)(2)(3)(4). The incidence of such autoantibodies in older individuals with diabetes, in individuals who are family members of patients with diabetes, and those who are islet cell antibody (ICA) positive appears to be more common than in the general population (5).…”
mentioning
confidence: 99%
“…In the latter case the level of TSH bioactivity was normal. Other examples in which circulating antibodies to the hormone could give rise to misleading immunoassays are autoantibodies to insulin (Wilkin & Nicholson, 1984).…”
Section: ) Circulating Antibodies To Hormonementioning
confidence: 99%